Enhanced Bioavailability of Boswellic Acid by Piper longum: A Computational and Pharmacokinetic Study - Vijayarani, K. Reeta; Govindarajulu, Manoj; Ramesh, Sindhu; Alturki, Mansour; Majrashi, Mohammed; Fujihashi, Ayaka; Almaghrabi, Mohammed; Kirubakaran, N.; Ren, Jun; Babu, R. Jayachandra; Smith, Forrest; Moore, Timothy; et al. (Frontiers in Pharmacology, 2020)
Chronic inflammation is a key culprit factor in the onset and progression of cardiovascular diseases such as atherosclerosis, myocardial infarction, and heart failure. Novel and pharmacologically effective therapeutic approaches are needed for new treatment remedy or improved pharmacokinetics and pharmacodynamics for existing synthetic drugs, in particular natural products. Boswellic acids are well-known natural products, with capacity to effectively retard inflammation without severe adverse effects. However, the therapeutic use of Boswellic acids are greatly hindered by its poor pharmacokinetic and pharmacodynamic properties. Co-administration strategies that facilitate the oral absorption and distribution of Boswellic acids should lead to a safe and more effective use of this product prophylactically and therapeutically in inflammation in cardiovascular diseases. In this study, we examined the effect of Piper longum extract on the absorption and bioavailability of Boswellic acid in rabbits. In addition, we further explored computational pharmacodynamic interactions between Piper longum and Boswellic acid. Piper longum extract at 2.5 and 10 mg/kg, dose-dependently increased the bioavailability of Boswellic acid (p<0.05). Based on our drug-based computational modeling, cytochrome P450 (CYP450)-mediated mechanism was involved in increased bioavailability. These findings confirmed that Piper longum with Boswellic may be administered orally together for effective therapeutic efficacy. Thus, our studies support the application of Piper longum with Boswellic acid as a novel therapeutic avenue in cardiovascular inflammatory disorders.